2002
DOI: 10.1034/j.1600-0625.2002.110408.x
|View full text |Cite
|
Sign up to set email alerts
|

Dual role of protein kinase C on mitogen‐activated protein kinase activation and human keratinocyte proliferation

Abstract: Subconfluent normal human keratinocytes exhibit autonomous (autocrine growth factor driven) proliferation and express the specific markers for keratinocyte proliferation K#5 and K#14. In keratinocyte autocrine culture, the exogenously added epidermal growth factor (EGF) has no effect on cell proliferation and mitogen-activated protein kinase (MAPK) activity. PD98059 inhibits MAPK pathway and autocrine keratinocyte proliferation. Staurosporine and Gö6976 strongly inhibit autonomous keratinocyte proliferation. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
0
11
1
Order By: Relevance
“…The activation of the IP 3 pathway, leading to intracellular calcium rise, is now accepted to be a key pathway linking intracellular Ca 2ϩ rise to ERK1/2 phosphorylation (15). Subsequent activation of CaM kinase II has also been linked to ERK1/2 activation in keratinocytes (14,54,55). Similarly, in the brain, this kinase plays a fundamental role in neuronal development and function (56 -59).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of the IP 3 pathway, leading to intracellular calcium rise, is now accepted to be a key pathway linking intracellular Ca 2ϩ rise to ERK1/2 phosphorylation (15). Subsequent activation of CaM kinase II has also been linked to ERK1/2 activation in keratinocytes (14,54,55). Similarly, in the brain, this kinase plays a fundamental role in neuronal development and function (56 -59).…”
Section: Discussionmentioning
confidence: 99%
“…Conditioned medium (CM) produced by NHKs stimulates DNA synthesis in a way that can be partially blocked with antibodies against various ErbB ligands and strongly blocked by antibodies against ErbB1 (Coffey et al, 1987;Cook et al, 1991a;Pittelkow et al, 1993Pittelkow et al, , 1994Hashimoto et al, 1994;Shirakata et al, 2000). Moreover, we and others have observed that it is very difficult to obtain proliferative quiescence in NHKs by removal of growth factors (GFs) (Coffey et al, 1987;Klein et al, 1992;Praskova et al, 2002). Together, these findings are strongly suggestive of an autocrine mechanism of ErbB activation in NHKs.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this role, studies from our group show that the novel PKC (nPKC) isoforms stimulate keratinocyte differentiation by activating MAPK signaling, which results in increased nuclear levels of AP1, CCAAT enhancer-binding protein, and Sp1 transcription factors and binding of these factors to target genes to increase transcription (27)(28)(29). Involucrin is a classical marker of differentiation, and our studies show that PKC␦ is a potent activator of involucrin expression (21, 27, 30 -32).PKC isoforms have also been implicated in the regulation of keratinocyte proliferation (13,20,23,(33)(34)(35). This role is particularly important, because keratinocyte differentiation is associated with cessation of proliferation, and it would make mechanistic sense to have a common kinase activate both processes.…”
mentioning
confidence: 97%